2020
DOI: 10.1021/acsomega.9b03363
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Modeling and Optimization of CO2 Absorption into Piperazine Solutions Using RSM-CCD Methodology

Abstract: The present work evaluates and optimizes CO 2 absorption in a bubble column for the Pz-H 2 O−CO 2 system. We analyzed the impact of the different operating conditions on the hydrodynamic and mass-transfer performance. For the optimization of the process, variable conditions were used in the multivariate statistical method of response surface methodology. The central composite design is used to characterize the operating condition to fit the models by the least-squares method. The experimental data were fitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 52 publications
1
49
0
2
Order By: Relevance
“…These results confirmed that the predicted and actual values were in good agreement, with high acceptability of the models [23]. The adequate precision measures the signal to noise ratio, and the ratio value of 33.76 indicated an adequate signal (adeq precision >4) [24].…”
Section: Fit Statisticssupporting
confidence: 78%
“…These results confirmed that the predicted and actual values were in good agreement, with high acceptability of the models [23]. The adequate precision measures the signal to noise ratio, and the ratio value of 33.76 indicated an adequate signal (adeq precision >4) [24].…”
Section: Fit Statisticssupporting
confidence: 78%
“…A three-dimensional (3-D) graph can also be used to represent the RSM results [ 13 ]. As an example, Figures 13 , 14 , and 15 show the effect of some interactions (feed gas velocity-orifice diameter, orifice diameter-gas head, and mixing particle diameter-mixing particles loading) on the average air velocity in the three different regions of the contact system.…”
Section: Resultsmentioning
confidence: 99%
“…1 À 23701 x 2 2 À 5:691 x 2 3 À 382:1 x 2 4 À 35:36 x 2 5 þ 52:13 x 1 x 2 À 66:7 x 2 x 3 À 198:1 x 2 x 5 À 29:74 x 3 x 4 þ 4:05 x 3 x 5 À 93:9 x 4 x 5 (13) Time-averaged middle air velocity (m/s) ¼ 0:6581 þ 38:07 x 2 À 22:24 x 4 À 0:0397 x 2 1 À 7642 x 2 2 þ 4:122 x 2 3 þ 320:7 x 2 4 þ 9:33 x 2 5 À 0:4880x 1 x 3 þ 5:523 x 1 x 4 þ 3:442 x 1 x 5 þ 146:1 x 2 x 3 þ 1988 x 2 x 4 À 4:61 x 3 x 5 þ 53:7 x 4 x 5 (15) where x 1 , x 2 , x 3 , x 4 , and x 5 are coded variables.…”
Section: Influences Of Factors On Air Velocityunclassified
See 2 more Smart Citations